Low tech hacking : street smarts for security professionals - Wiles, Jack.; Gudaitis, Terry; Jabbusch, Jennifer; Rogers, Russ.; Lowther, Sean. (Waltham, Mass. : Syngress, 2012)
Criminals using hacking techniques can cost corporations, governments, and individuals millions of dollars each year. While the media focuses on the grand-scale attacks that have been planned for months and executed by teams and countries, there are thousands more that aren't broadcast. Low Tech Hacking focuses on the everyday hacks that, while simple in nature, actually add up to the most significant losses. Attackers are using common techniques like social engineering, wireless hacking, and targeting and surveillance to gain access to valuable data. This book contains detailed descriptions.
Social engineering: the ultimate low tech hacking threat -- Low tech vulnerabilities: physical security -- More about locks and ways to low tech hack them -- Low tech wireless hacking -- Low tech targeting and surveillance: how much could they find out about you? -- Low tech hacking for the penetration tester -- Low tech hacking and the law: where can you go for help? -- Information security awareness training: your most valuable countermeasure to employee risk.
Includes bibliographical references and index.
Keywords: Computer security; Hackers; Computer Security; Sécurité informatique; Pirates informatiques; Computers and IT; Hackers; Computer security